Role of biomarkers of cardiac remodeling, myofibrosis, and inflammation in assessment of disease severity in euvolemic patients with chronic stable heart failure - Andreasová, Táňa; Vránová, Jana; Vondráková, Dagmar; Sedláčková, Lenka; Zákostelská, Zuzana Jirásková; Neužil, Petr; Málek, Filip (The Journal of international medical research, 2020)
OBJECTIVE: This study aimed to determine the importance of biomarkers of chronic heart failure (CHF) for assessing disease severity in euvolemic stable patients. PATIENTS AND METHODS: N-terminal pro-B-type natriuretic peptide (NT-proBNP), growth differentiation factor (GDF)-15, galectin-3, cystatin-C, soluble suppression of tumorigenicity 2 (sST2), tissue type inhibitor of matrix metalloproteinase (TIMP)-1, and ceruloplasmin levels were measured in euvolemic patients with stable CHF. Severity of CHF was defined by echocardiographic and biochemical parameters. RESULTS: In 160 patients (123 men and 37 women, mean age: 65.8±12.2 years), we found strong associations between NT-proBNP and bilirubin levels (r = 0.434) and the estimated glomerular filtration rate (r = -0.321). GDF-15 and cystatin-C levels were significantly correlated with parameters of kidney function. In multivariable regression analysis, NT-proBNP levels were associated with the left ventricular ejection fraction and left ventricular end-systolic volume (coefficient of determination R2 = 0.777). Additionally, GDF-15 levels were correlated with urea levels (R2 = 0.742), and cystatin C levels were correlated with urea and bilirubin levels (R2 = 0.732). CONCLUSION: Besides NT-proBNP, GDF-15 and cystatin C are promising biomarkers for establishing the severity of disease in euvolemic patients with stable CHF.
Keywords: Stroke Volume; cystatin C; matrix metalloproteinases; zánět; Female; biologické markery; Biomarkers; ženské pohlaví; Heart Failure; funkce levé komory srdeční; lidé; srdeční selhání; Natriuretic Peptide, Brain; growth differentiation factor-15; Chronic heart failure; N-terminal pro-B-type natriuretic peptide; stupeň závažnosti nemoci; Ventricular Remodeling; urea; peptidové fragmenty; Inflammation; natriuretický peptid typu B; Male; Peptide Fragments; Aged; tepový objem; remodelace komor; galectin-3; lidé středního věku; senioři; mužské pohlaví; Severity of Illness Index; Middle Aged; Ventricular Function, Left; Humans